Demographic Status and Blood Group of Family Blood Donors with a Focus on Their Rejection - Dipta, Tashmim Farhana; Akter, Zakia; Datta, Anamika; Nahar, Quamrun; Islam, Md Ashadul (BIRDEM Medical Journal, 2017)
Background: The aim of donor selection should protect donors from any potential harm which may occur as a direct result of the donation process; secondly, shall protect recipients of blood transfusions from adverse effects, such as transmission of infectious diseases or other medical conditions and unwanted effects caused by any medications taken by the donor. Any reason for deferral, whether temporary or permanent, have been explained to the donor and recorded as per National Guideline and Blood Safety Law. Literature search showed there is dearth information on replacement blood donors in Bangladesh. So this study has been done to evaluate replacement family blood donors, exploring their demographic status, occupation, blood groups and why they were rejected during donor selection. Methods: This study was done to assess the demographic profile and blood group among family blood donors during donor selection. Age, weight, occupation, blood group and blood pressure have been explored among randomly selected two hundred ninety one blood donors attending Transfusion Medicine Department of BIRDEM as per Guideline. Results: Among them 261 (89.69%) were male and 30 (10.31%) were female with M±SD age 29±6 and 29±7 (yrs), respectively. Blood group of replacement family donors were, A positive (39.7%), B positive 90(32%), O positive 18 (6%), AB positive 39 (13%) majority (57.04%) were unmarried , 52.58% were doing business, while students were 29.90% and job holders were only 17.53%. Among nine deferred donors females were mainly rejected (89.28%) and the contributing factor was low blood pressure according to guideline. Finally 96.91% successful family blood donors donated blood for the patient party. Conclusion: Our study showed proper selection and following of blood donation guideline help to determine the eligibility to donate blood. Moreover, this pilot study may contribute in evaluation of Bangladeshi family blood donors those had positive blood group and negative serological markers as per WHO (World Health Organization) guideline for Bangladesh. Birdem Med J 2016; 6(2): 112-117